Handbook of seafood quality, safety and health applications - Alasalvar, Cesarettin (Wiley-Blackwell, 2011)
Edited by an international team of experts who are widely-published leaders in their field Offers a review of the latest thinking on safety and quality - particularly crucial in the seafood sector Examines the latest commercial opportunities with regards to the nutritional benefits of marine-derived foods